(untitled) (Iraqi Journal of Medical Sciences, 2004)
Background: The reduction of under-five, and particularly infant, mortality to its biological minimum is regarded as a universally desirable goal. Specific targets for reducing the infant mortality rate have been set by many governments and international organizations. Objectives: To identify the mortality rate and causes of death among the children admitted to Al-Kadhimiya Teaching Hospital throughout a 5 years period from Jan. 1997 to the end of Dec. 2001. Methods: A retrospective study was done in AL-Kadhimiya Teaching Hospital. It included all the children died during the study period. The age range was since birth till 14 years of age. Information was obtained from reviewing the medical records including age, sex, and cause of death as documented in the death certificate. They were classified into 5 age groups. Statistical analysis was done using chi square, any P value greater than 0.05 was regarded to be not significant. Results: The over all mortality rate was 80 per 1000 hospital admissions. Male constituted 59.48% of deaths and female 40.52%. The mortality rate increased from 75.97/1000 in 1997 to 83.27/1000 in 2001. The leading causes of death were: In the neonatal period (29.08% of all deaths), sepsis (37.07%), prematurity (23.60%) and congenital anomalies (19.66%). In the infancy period (23.37% of all deaths), congenital anomalies (26.57%), pneumonia (21.68%), and sepsis (18.88%). In the age group 1-5 years (20.75% of all deaths), congenital anomalies (25.20%), diarrhea (20.47%) and pneumonia (17.32%). In the age group 6-10 years (15.68% of all deaths), malignancy (22.92%), congenital anomalies (21.88%) and diarrhea (20.83%). In the age group 11-14 years (11.12% of all deaths) malignancy (26.47%), congenital anomalies (22.07%) and diarrhea (19.12%). Conclusion: Death in children below 5 years of age represents about 73.2% of total deaths. The average children mortality rate was 80 per 1000 which was more than that in 1997 (75.97 per 1000). The mortality rate among male children was more than that in female with a ratio of 1.5:1. Key words: Mortality rate, Children, Death. Iraqi J Med Sci, 2004; Vol. 3 (1): 80-84